2001
DOI: 10.1080/00033790010010475
|View full text |Cite
|
Sign up to set email alerts
|

L'Analyse chimique des végétaux: Le cas du quinquina

Abstract: En 1820 J. Pelletier et J.-B. Caventou, deux pharmaciens-chimistes fran †ais travaillant a ' l'Ecole de Pharmacie de Paris, extraient de l'e ! corce de quinquina une nouvelle substance : la quinine. Cet exemple nous permet d'illustrer le processus qui me ' ne du produit naturel brut a ' l'isolement d'un principe actif et a ' sa production industrielle sous forme de me ! dicament. Ceci nous autorise a ' discuter du de ! veloppement de l'analyse chimique en relation avec la pharmacie, l' histoire naturelle, la m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Quinine is a TAS2R agonist that was purified in 1820 ( 14 ). A large number of medical cases have reported that quinine is a drug specific for malarial fever ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quinine is a TAS2R agonist that was purified in 1820 ( 14 ). A large number of medical cases have reported that quinine is a drug specific for malarial fever ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cinchona alkaloids are an important group of compounds whose occurrence, [22,23] synthesis, [24 -28] and other aspects [29][30][31][32][33] have received a great deal of attention, but Pasteur's considerable and pioneering work on cinchona alkaloids has not been examined in detail in the relevant literature. Therefore, the present article undertakes an analysis of Pasteur's studies of these substances and closely relevant matters, but the massive literature on the wide-ranging aspects of the cinchona alkaloids will not be covered here.…”
Section: Introductionmentioning
confidence: 99%